PENGEMBANGAN PERPUSTAKAAN MELALUI APLIKASI TEKNOLOGI INFORMASI DAN PENINGKATAN PARTISIPASI MAHASISWA - Siti Zulaikha (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2011)
This research aimed to find out the development of the Faculty of Education (FIP) Library in the State University of Jakarta ( UNJ) in terms of the role of the Faculty Library in supporting the learning activities at the Faculty of Education, efforts done to develop the Faculty Library, the application of information technology and the students’ participation. To meet its purposes this research was conducted at the Faculty of Education (FIP) of the UNJ within 4 months with the samples covering 120 respondents selected from FIP students by random sampling technique. Research results showed that the FIP Library has not been managed properly. Although the Library facilities are quite complete, they are not well benefitted, the information technology is not much used to develop the Library and the students’ participation is seemingly low. The research provides a number of suggestions to develop the FIPLibrary.